Photophysics and morphology of a polyfluorene donor–acceptor triblock copolymer for solar cells. Issue 23 (25th September 2013) - Yan, Chao; Cadby, Ashley J.; Parnell, Andrew J.; Tang, Weihua; Skoda, Maximilian W. A.; Mohamad, David; King, Simon P.; Reynolds, Luke X.; Haque, Saif A.; Wang, Tao; Parnell, Steven R.; Holmes, Andrew B.; et al.
ABSTRACT We present a study of the optical, structural and device properties of a polyfluorene (PFM)‐based (PFM‐F8BT‐PFM) donor–acceptor triblock copolymer for use in an organic solar cell. Neutron reflectivity is employed to probe the vertical composition profile before and after thermal annealing while the crystallinity was examined using grazing incidence wide‐angle X‐ray. The absorption spectra and photoluminescence emission for the triblock and analogous blend of PFM with F8BT reveal a greater degree of intermixing in the triblock. However, the triblock copolymer exhibits exciplex emission, which necessitates a geminate polar pair; long‐lived exciplex states are detrimental in organic photovoltaic devices. The triplet yield in the triblock and the blend is estimated using photoinduced absorption, with the triblock copolymer generating a triplet population 20 times that of the blend. This is far from ideal as triplets are wasted states in organic photovoltaic devices and they can also act as scavengers of polarons reducing the efficiency even more. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1705–1718